Pengembangan Ide Kreatif dalam Produksi Dokumenter Televisi â€œRuang Asa: Kisah Difabel Kulon Progo, Sang Penggugah Harapanâ€ - Livya, Livya; Asiatun, Siti (Jurnal Ilmiah Multimedia dan Komunikasi, 2023)
Disability according to the World Health Organization (WHO) is a loss or abnormality whether it is physiological, psychological, or an abnormality of anatomical structure or function. This documentary work tells the story of a person with physical disabilities from Sidorejo Village, Lendah, Kulon Progo, namely Wahyu Adi Nugroho who lives with great hope and enthusiasm so that he can benefit the environment around him. Nugroho is the only hamlet in the Special Region of Yogyakarta with disabilities. The writer as a producer aims to eliminate discrimination and society's stigma against people with disabilities, inspire people with disabilities, and encourage the government to realize an inclusive Indonesia through the creation of a television documentary entitled Development of Creative Ideas in the Production of Television Documentary â€œRuang Asa: The Story Of Kulon Progo Diffability, Invoking Hopeâ€. Through observation, interviews, and documentation the authors develop creative ideas in accordance with the theory, namely an idea that has developed which results in innovation. The author applies the concept of expository-style portrait documentary, gender-different narrator, detailed subtitles, and motion graphics to clarify specific information in the documentary. Through the implementation of the development of creative ideas by the writer as a producer, he has implemented the development of creative ideas that are inspiring, educative, and entertaining.